Conversion of lipid into high-viscosity branched bio-lubricant base oil. Issue 21 (9th July 2020) - Chen, Shuang; Wu, Tingting; Zhao, Chen
Abstract : To produce high-quality bio-lubricant, we reported a novel approach using lipids as a raw material, the process involved selective hydrogenation to fatty alcohols, dehydration of fatty alcohols to α-olefins, coupled polymerization–hydrogenation reactions. Abstract : To produce a high-quality bio-lubricant with similar properties compared to poly-α-olefins (PAO) lubricants, we reported herein a novel approach using sustainable and cheap lipids as a raw material, and the process involved the following tandem steps: selective hydrogenation to fatty alcohols (99% yield), dehydration of fatty alcohols to C12 –C18 α-olefins (90% yield), and subsequent coupled polymerization–hydrogenation reactions (93% yield). A comb-type C32 –C36 bio-lubricant was produced with an overall carbon utilization of ca. 90%. Ru3 Sn7 alloy nanoclusters favored the adsorption of acids and esters, thereby allowing hydrogenation of the lipids to the corresponding fatty alcohols. The mixture of Lewis solid acids, such as Al2 O3 and ThO2, allowed for the selective dehydration of the alcohols to α-olefins. Al2 O3 catalyzed alcohol dehydration, while ThO2 selectively adsorbed α-olefins avoiding further isomerization. The polymerization of α-olefins and the subsequent hydrogenation steps were catalyzed by AlCl3 and Pd/C, respectively, resulting in a branched fully-synthetic C32 –C36 bio-lubricant. The main properties of the as-prepared bio-lubricant from coconut oil were similar to those of ExxonMobil 4T—a commercial high-viscosity PAO lubricant. This process provides a highly competitive and economic route for the conversion of abundant lipids into relevant bio-lubricant base oils.